(Il)logical knowledge management : a guide to knowledge management in the 21st Century - Weed-Schertzer, Beverly (Emerald points., 2020)
In finding the logical by way of the illogical in Knowledge Management strategy, this book highlights key challenges and opportunities for businesses looking to improving the efficacy and extent of their knowledge management infrastructure.